Low-level microsatellite instability occurs in most colorectal cancers and is a nonrandomly distributed quantitative trait. - Halford, S; Sasieni, P; Rowan, A; Wasan, H; Bodmer, W; Talbot, I; Hawkins, N; Ward, R; Tomlinson, I (2002)
About 10-15% of colorectal cancers show high-level microsatellite instability. The characteristics and very existence of low-level instability (MSI-L) are unclear, although some studies have found associations between MSI-L and molecular characteristics, notably more frequent K-ras mutations and a low level of allele loss near APC. We have attempted to define a MSI-L group of tumors by analyzing 107 sporadic colorectal carcinomas at 44 microsatellites. Ten (9.7%) MSI-H cancers were identified, but there was no evidence for a discrete MSI-L group. However, the 97 non-MSI-H cancers showed greater variation in the frequency of MSI than was expected by chance. Most cancers (68%) in the non-MSI-H group showed some MSI and could therefore be classed as nominally MSI-L. No association was found between MSI-L (or the level of MSI) and any clinicopathological or molecular variable, including K-ras mutation and loss of heterozygosity at APC. The causes of variation in level of the MSI in non-MSI-H colorectal cancers are unknown, but the differences are quantitative and probably reflect the evolutionary histories of the cancers rather than qualitatively different genetic pathways of tumorigenesis.